Negative air ions through the action of antioxidation, anti-inflammation, anti-apoptosis and angiogenesis ameliorate lipopolysaccharide induced acute lung injury and promote diabetic wound healing in rat - Cheng, Yu-Hsuan; Li, Hung-Keng; Yao, Chien-An; Huang, Jing-Ying; Sung, Yi-Ting; Chung, Shiu-Dong; Chien, Chiang-Ting (PLOS ONE, 2022)
Negative air ions (NAIs) being bioactive and negative charged molecules may confer antioxidant and anti-inflammatory activity. We assessed the effect of NAIs on two inflammatory diseases in animal models including lipopolysaccharide (LPS) induced acute lung injury (ALI) and wound healing in diabetic rats. We used intra-tracheal infusion of LPS to induce ALI and made a full-thickness cutaneous wound in streptozotocin-induced diabetic female Wistar rats. We evaluated NAIs effects on reactive oxygen species amount, leukocyte infiltration, wound healing rate, western blot, and immunohistochemistry in the lungs of ALI and skin sections of wounds. Our data found NAIs exposed saline displayed higher antioxidant activity vs. non-exposed saline. NAIs exposure did not significantly affect arterial blood pressure and respiratory frequency in control and LPS treated groups. LPS increased leukocyte infiltration, caspase 3/Poly-ADP-ribose-polymerase-mediated apoptosis formation and decreased Beclin-1/LC3-II-mediated autophagy in lungs. NAIs exposure conferred pulmonary protection by depressed leukocyte infiltration and caspase 3/Poly-ADP-ribose-polymerase mediated apoptosis and enhanced LC3-II-mediated autophagy in LPS induced ALI. NAIs treatment resulted in a significantly accelerated wound closure rate, decreased erythrocyte accumulation and leukocyte infiltration mediated oxidative stress and inflammation, and upregulated expression of skin collagen, vascular endothelial growth factor receptor-2 (VEGFR-2) and factor transforming growth factor-beta 1 (TGF-β1) vs non-treated group. Based on these results, it is suggested that NAIs conferred a protection through the upregulating LC3-II-dependent autophagy mechanism and downregulating leukocyte infiltration mediated inflammation and caspase 3/Poly-ADP-ribose-polymerase signaling in the LPS-treated ALI and promoted diabetic wound healing through the enhancing skin collagen synthesis, VEGFR-2 and TGF-β1 pathways.